Fracture prediction with modified-FRAX in older HIV-infected and uninfected men. - Yin, Michael T; Shiau, Stephanie; Rimland, David; Gibert, Cynthia L; Bedimo, Roger J; Rodriguez-Barradas, Maria C; Harwood, Katherine; Aschheim, Josh; Justice, Amy C; Womack, Julie A (Journal of acquired immune deficiency syndromes (1999), 2016)
FRAX® is a validated, computer-based clinical fracture risk calculator that estimates 10-year risk of major osteoporotic (clinical spine, forearm, hip or shoulder) fracture, and hip fracture alone. It is widely used for decision-making in fracture prevention, but may underestimate risk in HIV-infected individuals. Some experts recommend considering HIV a cause of secondary osteoporosis when calculating FRAX in HIV-infected individuals.